Worship in a post-lockdown context: A ritual-liturgical perspective - Scott, Hilton R. (HTS teologiese studies, 2020)
In this unprecedented time, there are many questions and plenty of speculation surrounding what life will be like after the South African nationwide lockdown. There is concern over the effects that the lockdown will have on worship services when churches are in a position to open their doors to the public once more. As a result of recognising the lockdown as a liminal phase, perspectives are shared when considering how the church will gather again in a post-lockdown context and therefore a post-liminal phase. One prevailing perspective in considering this post-liminal phase involves koinonia and how an undiscriminating virus can remind those to further practise inclusivity and ubuntu, by embracing sameness and difference when ‘being church’. In contrast, another important perspective focuses on ritualising certain measures in the worship service to prevent the spread of coronavirus disease 2019 (COVID-19), when gathering in church buildings is permissible in a post-lockdown context. This is concluded by echoing the spirit of ubuntu, namely, ‘I am because we are’, in ‘being church’ during and after the crisis of the COVID-19 global pandemic.Contribution: From the perspective of Liturgical and Ritual Studies, this article aims to contribute to the Theological perspectives of COVID-19.